1991
DOI: 10.1103/physrevlett.67.1906
|View full text |Cite
|
Sign up to set email alerts
|

New mechanism for electron-stimulated desorption of nonthermal halogen atoms from alkali-halide surfaces

Abstract: Fully angular-resolved kinetic-energy distributions of alkali and halogen atoms emitted due to electron-stimulated desorption have been measured for (100) and (110) alkali-halide surfaces. An unexpected strong directional emission of nonthermal halogen atoms along the (100) axis of the investigated crystals has been found which is in contradiction to the predictions of the previously proposed "Pooley model." We propose a new model involving diffusion of hot holes to the surface, and sudden localization of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…Angle resolved ESD measurements of KCl and KBr single crystals demonstrated a strong directional emission of the hyperthermal component along the ͗100͘ axis. To explain this result, the concept of hot hole diffusion in the bulk followed by hole localization at the surface was introduced [10]. Recent experiments on epitaxially grown alkali-halide thin films were explained in terms of hot excitons [11].…”
mentioning
confidence: 99%
“…Angle resolved ESD measurements of KCl and KBr single crystals demonstrated a strong directional emission of the hyperthermal component along the ͗100͘ axis. To explain this result, the concept of hot hole diffusion in the bulk followed by hole localization at the surface was introduced [10]. Recent experiments on epitaxially grown alkali-halide thin films were explained in terms of hot excitons [11].…”
mentioning
confidence: 99%
“…It has been demonstrated in many experiments [20][21][22], that the TOF spectra of halogen atoms consist of two components: the thermal (which can be fitted with a Maxwellian distribution function) and the non-thermal one. The non-thermal peak, at energy of about 0.25 eV, corresponds to the halogen atoms emitted as a result of the decay of self-trapped excitons at the surface.…”
Section: Resultsmentioning
confidence: 99%
“…The details of this mechanism are still debated. It is commonly believed that emission of atoms is due to F and H centre formation, its subsequent diffusion to the surface and annihilation followed by thermal evaporation [8,17]. Desorption events are belived to take place most likely at step edges and corners because the amount of energy gained from defect annihilation is rather small.…”
Section: Resultsmentioning
confidence: 99%
“…However, structure of the yields measured for alkali halides cannot be explained completely by the Auger decay model. Furthermore, recent experiments have shown that the ESD could involve surface exciton decay as well [7][8][9]. Therefore for the unambiguous identification of the processes involved precise measurements of threshold energies are required.…”
Section: Introductionmentioning
confidence: 99%